Effect of amino acid infusion on perioperative thermoregulation in newborn surgery - Okumuş, Mustafa; Salman, Faik Tansu (The European Research Journal, 2021)
Objectives: Decreased drug metabolism, coagulation disorders, wound infections, and cardiac arrhythmias are the most important and well-known results of intraoperative hypothermia. Perioperative amino acid infusion is known to prevent intraoperative hypothermia during general anesthesia in adults. In this study, we aimed to demonstrate the effect of perioperative amino acid infusion on the prevention of hypothermia during general anesthesia in newborn surgery.Methods: Twenty surgical newborns, aged 1-30 days, were enrolled in this prospective randomized controlled study. Newborns were assigned randomly into two groups: the amino acid/dextrose (AAD) group and the dextrose (D) group. The core temperatures of the newborns were measured from the distal esophagus in the first minute of the induction once and every fifteen minutes thereafter. The core body temperature changes in each group during the operation and the differences between the two groups were analyzed.Results: The surgical operations in each group were similar. The mean operating room temperatures of AAD and D groups were 25.4 ± 0.2°C and 25.3 ± 0.3°C, respectively. There were no significant differences in the general characteristics of the two groups. The mean core temperatures began to decrease after the induction of anesthesia in both groups and continued to decrease during the course of the surgery. There was no significant difference between the two groups.Conclusions: Hypothermia develops in all neonates when surgical time exceeds one hour, even in warmer ambient temperatures. Although it seems effective in adults, amino acid-induced thermoregulation does not seem effective in newborns during general anesthesia.